A novel chitosan/wheat gluten biofoam fabricated by spontaneous mixing and vacuum-drying. Issue 114 (3rd November 2015) - Chen, F.; Gällstedt, M.; Olsson, R. T.; Gedde, U. W.; Hedenqvist, M. S.
Abstract : The pore formation and its structure. Abstract : A new type of chitosan and wheat gluten biofoam is presented. The pore structure achieved relied solely on the specific mixing and phase distribution when a film was cast from an aqueous mixture of chitosan/wheat gluten solution, in the absence of any chemical blowing agent, porogen or expanding gas. The foam was obtained when the liquid phase was removed by vacuum drying, without the need for the traditional freeze-drying that is frequently used for pore formation. Soft foam samples could be prepared with stiffnesses from 0.3 to 1.2 MPa and a high rebound resilience (64 and 94% at compressive strains of 80 and 20%, respectively). The foams were relatively ductile and did not require any plasticiser to allow for in-plane deformation (20% compression) and smaller bending. Only open pores with sizes of the order of 70–80 μm were observed by microscopy. The density of all the foams was ∼50 kg m −3, due to the high porosity (96% air). The foams showed a rapid and large uptake of both non-polar (limonene) and polar (water) liquids. When immersed in these liquids for 1 second, the maximum uptake recorded was 40 times the initial mass of the foam for limonene and 8 times for water.